Fracture toughness evaluation of a cracked au thin film by applying a finite element analysis and bulge test - Tinoco, Hector A.; Hutař, Pavel; Merle, Benoit; Göken, Mathias; Kruml, Tomas (Key Engineering Materials, 2020)
This paper presents a finite element analysis of a pre-cracked freestanding gold thin film subjected to bulge test. These tests were conducted in order to determine the elasto-plastic properties and fracture toughness of the gold films. For the experimental tests, a pre-crack was introduced in the center of the film by focused ion beam (FIB) milling with a length of 10 µ m and a width of 100nm. For the numerical fracture analysis, the problem was divided into two stages; the first stage was the development of the numerical model on the whole film without pre-crack (elasto-plastic analysis) and the second one was performed on a film portion that included the pre-crack (sub-modeling stage). Three different notches (rounded, sharp and V-sharp) were applied to calculate the stress intensity factor around the crack tip using path independent J-integral. The obtained results show that the load-deflection curves for non-cracked and pre-cracked film reproduced the experiments using the calculated elasto-plastic properties. This indicates that the proposed models presented a good correlation and robustness. Additionally, fracture toughness values were calculated between 0.288 0.5 and 0.303 MPa. m0.5 with J-integral values 1.037 J/m2 (elastic) and 1.136 J/m2 (elasto-plastic) which correspond with other calculations available in the literature.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Bulge test; Finite element analysis; Fracture toughness; Gold film; Thin films